Reinterpreting Heroism: A queer Lens on Madeline Miller’s The Song of Achilles - Tamba, Mariana Cecillia; Siregar, Lailan Haz Anugrahyuni; Valerie, Clairin; Yudhea, Fasya; Syahputra, Fikry Prastya (Journal of English Language and Education, 2025)
This study explores the redefinition of heroism and queer identity in Madeline Miller's The Song of Achilles, highlighting its importance in contemporary literature. While previous research focuses on romantic and queer elements, it often overlooks how the novel systematically challenges traditional views of heroism, especially through emotional vulnerability and mentorship. Few analyses examine how Miller critiques conventional ideas of heroism by emphasizing compassion and self-acceptance. Using a qualitative descriptive approach and close reading, this study examines key themes such as love and emotional connections. The findings reveal that true heroism is rooted in these connections rather than physical strength, showing how the bond between Achilles and Patroclus reflects empathy and community. Ultimately, Miller's work encourages a broader understanding of heroism, suggesting it includes the courage to embrace one's identity, enriching discussions in literary studies and beyond.